Plastic Composites Using Mango Leaf Waste for Cost Effectiveness and Green Environment - Rahmat Satoto; Rijal Ahmadi; Dadi Rusdiana; Erni Ernawaty; Anung Syampurwadi; Akbar Hanif Dawam Abdullah (Syarif Hidayatullah State Islamic University, 2022)
Due to ecological considerations, natural biodegradation composites are widespread in tailoring plastics properties to specific needs. This work aims to demonstrate the available opportunity in using 100 and 140 mesh powdered mango leaf (PML) waste as a filler in polypropylene (PP) composites. Composites were produced via melt blending on a twin-screw internal mixer, with a different particulate size and a weight ratio of PML. Morphology, tensile, flexural, hardness, tear, puncture, thermal, and water absorption properties of the composites were assessed after 0, 1, 7, 14, and 28 days of water immersion. We found that the smaller particle size shows a better mechanical and water absorption of the composites, but not for thermal properties. The mechanical properties decreased with increasing PML content; however, these properties did not differ considerably from pure PP and other composites with natural filler. Besides, these polypropylene/PML composites showed excellent properties in water absorption.